TRANSFORMASI KUDUS SEBAGAI KOTA LAYAK ANAK ( Tinjauan atas Pemenuhan Hak Sipil dan Partisipasi ) - Siti Malaiha Dewi (UIN K.H. Abdurrahman Wahid Pekalongan, 2011)
Abstract: Children are a gift of God's mandate and at the same time that always must be maintained. Unfortunately, some cases such as child exploitation, child sexual abuse, trafficking, was just always there. In fact, the City of Eligible Children (KLA) has long been proclaimed. Kudus, is one of them. The research is to know